2024
DOI: 10.3389/fmats.2024.1374409
|View full text |Cite
|
Sign up to set email alerts
|

Integration of BMP-2/PLGA microspheres with the 3D printed PLGA/CaSO4 scaffold enhances bone regeneration

Li Zhao,
Xiaoliang Zhao,
Fengpiao Deng
et al.

Abstract: Treatment of large and complex irregular bone defects is a major clinical challenge in orthopedic surgery. The current treatment includes bone transportation using the Ilizarov technique and bone cement repair using the Masquelet technique, but they require long-term manual intervention or secondary operation. To improve this situation, we compared the different implanting materials in the literature published in the past 10 years, finding that glycolic acid copolymer (PLGA) and Calcium sulfate (CaSO4) are app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Among these, encapsulation is one common technique, where growth factors are entrapped within biodegradable microspheres or nanoparticles dispersed throughout the scaffold matrix, allowing for a sustained release. Recent in vitro studies by Zhao et al demonstrated that BMP-2 encapsulated in PLGA microspheres when integrated into a 3D printed PLGA/CaSO 4 scaffold, significantly promoted osteogenic differentiation over an extended period [ 126 ].…”
Section: Scaffold Fabrication Techniquesmentioning
confidence: 99%
“…Among these, encapsulation is one common technique, where growth factors are entrapped within biodegradable microspheres or nanoparticles dispersed throughout the scaffold matrix, allowing for a sustained release. Recent in vitro studies by Zhao et al demonstrated that BMP-2 encapsulated in PLGA microspheres when integrated into a 3D printed PLGA/CaSO 4 scaffold, significantly promoted osteogenic differentiation over an extended period [ 126 ].…”
Section: Scaffold Fabrication Techniquesmentioning
confidence: 99%
“…These imaging data provide invaluable insights into the size, shape, location, and surrounding tissue architecture of the defect. Based on these data, additive manufacturing technologies such as 3D printing can be leveraged, wherein NFMS can possibly be integrated as part of the “bio-ink” that forms patient-specific NFMS-integrated scaffolds. , As it would be designed to closely match the dimensions and contours of the patient’s bone defect, it would promote optimal fit and contact with the surrounding tissue for improved integration and functionality. , Bioactive factors can be incorporated into the NFMS matrix using spatially controlled deposition methods, allowing for the creation of gradient or multilayered scaffolds that mimic the native tissue microenvironment and promote enhanced tissue regeneration . Moreover, personalized NFMS-based therapies can harness patient-derived cells and bioactive factors to further augment bone healing outcomes.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%